Being overweight and obese increases suicide risk, the severity of depression, and the inflammatory response in adolescents with major depressive disorders - Ninla-aesong, Putrada; Puangsri, Pavarud; Kietdumrongwong, Pongtorn; Jongkrijak, Haruthai; Noipha, Kusumarn (Frontiers in Immunology, 2023)
Background: There is a bidirectional relationship between obesity and depression. We investigated whether the coexistence of obesity and depression increases the risk of having severe depression and a high suicide risk in adolescents with major depressive disorder (MDD).Additionally, we explored the potential mechanisms linking the coexistence of obesity and depression to worse outcomes in these patients.The odds of high suicide risk and severe depression were compared among MDD patients based on different body mass index (BMI) groups. Complete blood count (CBC) parameters, inflammatory ratios (neutrophil-lymphocyte ratio [NLR], monocyte-lymphocyte ratio[MLR], and platelet-lymphocyte ratio [PLR]), and cytokine levels (IFN-, IL-1, IL-6, IL-8, MCP-1, TNF-, and TGF-1) were evaluated across BMI groups. Additionally, Pearson correlation coefficients (r) were assessed to understand the relationships between the 8Q and 9Q scores, CBC parameters, inflammatory ratios, cytokine levels, and BMI.Results: A total of 135 antidepressant-naive adolescents with MDD were included. Overweight and obese MDD patients had higher odds of having high suicide risk and severe depression than lean individuals. Furthermore, they exhibited significantly higher white blood cell (WBC), and neutrophil counts. The NLR tended to be higher in obese MDD patients than in leans. Overweight and obese MDD patients had elevated levels of interleukin (IL)-1 and IL-6 compared to lean individuals, while TGF-β1 levels appeared to decline as body weight increased. BMI showed weak positive correlations with 8Q score, WBC count, neutrophil count, monocyte count, platelet count, neutrophil percentage, and NLR, and a weak negative correlation with 3 lymphocyte percentage. The 8Q score displayed weak positive correlations with BMI, neutrophil percentage, monocyte percentages, NLR, and MLR, and a weak negative correlation with lymphocyte percentage.The findings suggest that coexistence of overweight or obesity with depression heightened inflammatory responses, leading to worse outcomes and increased suicide risk in adolescents MDD patients.